The factoring of the expression x²=-x+6 is (x-2)(x+3)
By ordering the values, we get:
x² + x - 6 = 0
To solve this exercise, we have to follow the rules of factoring:
1. Looking for the a and b number that state the following equations:
Analyzing that (a*b) is a negative number, it means that (a) and (b) have different signs, and due to the results of (a+b) is positive the higher number has to be the positive one.
The number could be:
a = -2
b = 3
Confirming:
a + b = -2 + 3 = 1
a * b = (-2) * 3 = - 6
2. Rewriting the factored expression (x+a)(x+b) with the obtained values, we get:
(x-2)(x+3)
<h3>What is factoring?</h3>
Is a technique that consist of decomposition of a factor into a product of another factor, which when multiplied together give the original number.
Learn more about factoring at brainly.com/question/24734894
#SPJ4
Answer:
D
Step-by-step explanation:
Answer:
A rectangle has four right angles, A triangle has 3 sides, A square has 4 equal sides
Step-by-step explanation:
Answer:
.
Step-by-step explanation:
Answer:
i think 40 meters
Step-by-step explanation:
i hope this helps